Chikungunya (Togaviridae) and dengue 2 (Flaviviridae) viruses detected from Aedes aegypti mosquitoes in Burkina Faso by qRT-PCR technique: Preliminary results and perspective for molecular characterization of arbovirus circulation in vector populations - Hien, Aristide S.; Sangaré, Ibrahim; Ouattara, Eric L. Parfait; Sawadogo, Simon P.; Soma, Diloma D.; Maiga, Hamidou; Diabaté, Abdoulaye; Bonnet, Emmanuel; Ridde, Valéry; Fournet, Florence; Hawkes, Frances M.; Kaupra, Carina; et al. (Frontiers in Tropical Diseases, 2022)
In 2016, we conducted an entomological survey in a railway transect between Banfora and Ouagadougou, Burkina Faso. The aim was to evaluate the risk factors for arbovirus epidemics, including vector infection status, in areas representative of the country. Aedes aegypti mosquitoes were collected at larval stage from their natural rearing habitats in four study sites when estimating the main larval index, and reared until adult stage and kept in RNAlater for detection of arbovirus RNA. In the laboratory, the mosquito specimens were screened for dengue virus (DENV) and chikungunya virus (CHIKV) using one step real-time qRT-PCR. We detected one DENV-2 positive pool from Ouagadougou, giving a minimum infection rate (MIR) of 1.67, and 6 CHIKV positive pools, giving a MIR of 6.67 from Ouagadougou, but also in Banfora and Boromo. This qRT-PCR approach, if validated with diversified samples including also wild blood fed adults, is a useful tool for arboviruses circulation and disease surveillance in Burkina Faso.